Enhancing Management Control Through ERP Systems: A Comprehensive Literature Review - Hammouch, Hind (iRASD Journal of Management, 2024)
This article examines the significant impact of ERP (Enterprise Resource Planning) on management control in modern organizations, based on the Marroy case study. Exploring the deep integration between ERP and critical management control functions, this essay offers an in-depth analysis of key benefits such as task automation, business process optimization, and improved decision-making. The study highlights the challenges associated with ERP implementation, and proposes effective solutions for maximizing the benefits of this technology in the context of today's digital transformation. By offering an essential perspective on the evolution of management control practices thanks to the technological innovations of ERP, this article contributes to the understanding of modern strategic and operational strategies in organizations.